Understanding urban consumers’ food choice behavior in Ethiopia: Promoting demand for healthy foods - Melesse, Mequanint B.; Van den berg, Marrit; de Brauw, Alan; Abate, Gashaw T. (International Food Policy Research Institute, 2019)
Using survey data collected from 996 representative households in Addis Ababa, Ethiopia, this paper documents several insights to help understand urban consumer food purchasing and consumption choices. The findings can be summarized as follows: 1) We find that households face important dietary gaps; a large proportion eats insufficient amounts of nutrient-dense vegetables, animal-source foods, and fruits. 2) The consumption of ultra-processed foods increases with income and may become a pressing health concern as incomes rise. 3) From a purchasing perspective, we find that consumers buy foods for different purposes at different outlets. Nearby kiosks and informal street markets are frequented for small food items and for fruits and vegetables, while formal open markets and consumer cooperatives are used for bulky food items. 4) Respondents make food and food outlet choices based on their health and food safety concerns, but few consider the nutritional value of food when purchasing it. Concurrently, the availability of a wide variety of healthy and safe foods is highly valued by most respondents for outlet choice. Among consumers in lower income categories, they tend to make food and food outlet choices based on prices and location convenience. 5) Although nutrition is not a primary concern when making choices about food, consumers appear to have reasonable nutritional knowledge. Most respondents considered a healthy diet to be primarily plant-based. Most people are aware that they should eat more fruits and vegetables and less sugary, fatty, and salty foods, but they have limited knowledge on the nutrient content of specific foods and the causes of obesity. 6) Labelling would not be an effective way to increase nutritional knowledge; most respondents have limited understanding of the information that labels provide. Rather, most respondents trust the information provided by health professionals over other sources. In sum, these results are potentially relevant for policy and the design of future programs for improving nutritional outcomes through enhanced diets.